Participation of eIF4F complex in Junin virus infection: blockage of eIF4E does not impair virus replication - Linero, Florencia Natalia (2013)
Translation efficiency of viral mRNAs is a key factor defining both cytopathogenicity and virulence of viruses, which are entirely dependent on the cellular translation machinery to synthesize their proteins. This dependence has led them to develop different translational reprogramming strategies to ensure viral mRNAs can effectively compete with cellular mRNAs. Junin virus (JUNV) is a member of the family Arenaviridae, whose mRNAs are capped but not polyadenylated. In this work we evaluated the relevance to JUNV replication of the main components of the eIF4F complex: eIF4A, eIF4GI and eIF4E. We found the viral nucleoprotein (N) of JUNV colocalized with eIF4A and eIF4GI but not with eIF4E. Moreover, N could be immunoprecipitated in association with eIF4A and eIF4GI but not with eIF4E. Accordingly, functional impairment of eIF4A as well as eIF4GI reduced JUNV multiplication. By contrast, inhibition of eIF4E did not show a significant effect on JUNV protein synthesis. A similar situation was observed for another two members of arenaviruses: Tacaribe (TCRV) and Pichinde (PICV) viruses. Finally, the nucleoproteins of JUNV, TCRV and PICV were able to interact with 7 methyl-guanosine (cap), suggesting that the independence of JUNV multiplication on eIF4E, the cap-binding protein, may be due to the replacement of this factor by N protein.